(3GdebGeGJ GdRjfjIs - (3eYO Hf fUQ Gddg Hf QLH, CHh GdfOj TeS GdOjf GHf CHj GdaJM, GdeYQha HGHf GdUjbd GdLRQj,J (B701 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj ONdJ PGJ jhe NjSj, hChjJ CfjSj s
(3BNQgG (B:s
(3hJZQjO GdeYGfj HGdeZGfj dCLYdg LhfG fWde GdeJTGHgGJ s
(3fSNI KGfjIs
(3ChQGbgG GdCNjQI HNW CMOKs
(3hJJab aj ChdgG eY Chd GdfSNI GdChdis
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B304 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B465s
Keywords: (3GdCOHs